SUSTAINABLE REPORTING FOR AGRICULTURAL COOPERATIVES KEY INSIGHTS AND FRAMEWORK DEVELOPMENT - Iryani, Lia Dahlia (Journal of Environmental Science and Sustainable Development, 2023)
A study on the viability of implementing sustainable reporting in Indonesian agricultural cooperatives is exceptionally uncommon, given the underlying concerns raised by the Financial Services Authority (OJK) Regulation No. 51/2017. In order to help achieve the Sustainable Development Goals, this project intends to investigate the potential of indicators of economic, ecological, and social sustainability. Employing the Analysis of Variance (ANOVA) method, this study analyzes the content of 85 sustainability reports using the Global Reporting Initiative (GRI) G4 reporting framework to determine the correlations between different sustainability categories and how they affect agribusiness and evaluate the impact on the business. The majority of agricultural firms exhibit a strong positive association between economic, environmental, and social performance measures, as demonstrated by the results and discussion. However, the environmental and human rights categories have a weak and marginal correlation in economic practices, employment, and decent work. These results suggest that improved economic performance can contribute to agribusiness's environmental and social performance. This study confirms the feasibility of implementing sustainable reporting in Indonesian agricultural cooperatives. This study emphasizes the necessity of a thorough and uniform reporting structure that successfully incorporates sustainability's social, environmental, and economic facets. The results provide valuable insights for Indonesian agricultural cooperatives who want to improve their sustainability practices and contribute to sustainable development. Cooperatives are encouraged to adopt sustainability reporting practices to improve transparency, accountability, and overall impact on economic, environmental, and social dimensions.